Hubungan Dukungan Keluarga Dengan Pemberian Asi Ekslusif Pada Ibu Menyusui Di Wilayah Kerja Puskesmas L. Sidoharjo Kabupaten Musi Rawas Sumatera Selatan - Widi Astuti, Uci; Yulianti, Syami; Ayudiah, Febra (Jurnal Pakar Kesehatan, 2025)
Word Health Organisation (WHO) research in 2020, recommends that all infants are recommended to be exclusively breastfed until the age of six months because breast milk is the gold standard of nutritional value for infants. Infants who are not breastfed will be at risk of various infectious diseases. Infectious diseases that often occur in infants include diarrhoea. Support or support from others or people closest to you plays a role in the success or failure of breastfeeding. The purpose of this study was to determine the existence of family support with exclusive breastfeeding in breastfeeding mothers at Puskesmas L. Sidoharjo, Musi Rawas Regency, South Sumatra. This study is a correlational analytic study with a cross sectional approach, a sample size of 59 couples. Data analysis used univariate in the form of frequency distribution and bivariate using the Chi Square test with a significance level of p <0.05. The results showed that most families were less supportive of exclusive breastfeeding, most of them gave exclusive breastfeeding to their babies, and there was a relationship between family support and exclusive breastfeeding.The researcher suggested health workers to increase the coverage of exclusive breastfeeding by motivating mothers to apply the knowledge they have about exclusive breastfeeding in the form of real behaviour, namely providing exclusive breastfeeding to their babies.